2002
DOI: 10.1124/jpet.102.044818
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Neurologic and Behavioral Effects of Subtoxic Doses of Cholinesterase Inhibitors

Abstract: We tested the hypothesis that pyridostigmine bromide (PB) intake and/or low-level sarin exposure, suggested by some as causes of the symptoms experienced by Persian Gulf War veterans, induce neurobehavioral dysfunction that outlasts their effects on cholinesterase. Adult male Sprague-Dawley rats were treated during 3 weeks with s.c. saline, PB in drinking water (80 mg/l), sarin (62.5 g/kg; 0.5ϫ LD 50 , three times/week s.c.), or PB in drinking water ϩ sarin. Animals were tested for passive avoidance, nocicepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 35 publications
5
12
2
Order By: Relevance
“…The ChE activity values returned to normal 3 weeks after the last exposure. Similar to our findings, Scremin et al (2003) observed recovery of blood ChE activity in rats after 2-3 weeks after discontinuation of sarin treatment. Roberson et al (2005) also reported a significant decrease of AChE after repeated exposures to sarin in guinea pigs with a return to non-significant differences 30-100 days after the last exposure.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The ChE activity values returned to normal 3 weeks after the last exposure. Similar to our findings, Scremin et al (2003) observed recovery of blood ChE activity in rats after 2-3 weeks after discontinuation of sarin treatment. Roberson et al (2005) also reported a significant decrease of AChE after repeated exposures to sarin in guinea pigs with a return to non-significant differences 30-100 days after the last exposure.…”
Section: Discussionsupporting
confidence: 94%
“…In this study no change in ASR or PPI was found after sarin administration, even though red blood cell ChE activity was significantly decreased. Differences in the modulation of ASR by organophosphates among rodent species (mice, rats and guinea-pigs) have been described by many authors (Scremin et al, 2003;Philippens et al, 1996Philippens et al, , 1997Jones and Shannon, 2000). These studies together with our results indicate the involvement of other than cholinergic systems in this modulation.…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with our previous work in rats (Shih, 1981;Shih and McDonough, 1997;Scremin et al, 2003;Shih et al, 2004), mice receiving a high dose of sarin (i.e., 1.0 x LD 50 dose) showed characteristic signs of convulsions. Mice treated with a 1.0 x LD 50 dose of sarin displayed a significant increase in the state of phosphorylation of the transcription factor CREB in striatum.…”
Section: Significance Of Findingssupporting
confidence: 79%
“…The appearance of increases in phospho(T75)-DARPP-32 levels at doses of sarin that are subthreshold for convulsion suggests that changes in signaling pathways that control phosphorylation of this site (e.g., CDK5) may mediate brain responses to nerve agents. Since CDK5 has been associated with normal neuronal development and with the structural reorganization of neurons in response to drugs of abuse (Bibb et al, 2001;Norrholm et al, 2003), it may be an excellent candidate for mediating the subtle, long-lasting perceptual and motor deficits associated with low-level sarin exposure (Scremin et al, 2003). However, the present studies did not show a similar effect of sub-threshold sarin on T75 phosphorylation in mice.…”
Section: Significance Of Findingscontrasting
confidence: 55%
“…Toxicologic animal studies have found that repetitive exposure to low, subsymptomatic doses of sarin (generally <0.3 LD50 or LCt50) produce long-lasting EEG changes in nonhuman primates [42], delayed alteration of brain acetylcholine receptors in rats [43], chronic behavior changes in rats [44,45], and autonomic disturbances in mice [46]. Van Helden et al [47] in a dose-finding pilot study further suggested that the lowest level of sarin exposure that permanently alters the EEG of nonhuman primates (0.1-0.2 mg min m -3 corresponding to a sarin concentration of 0.0073-0.014 mg m -3 ) may be at least an order of magnitude lower than the level that causes miosis or is detected by the M8A1 nerve agent alarm.…”
Section: Review Of Intelligence Data Relevant To Long-distance Transitmentioning
confidence: 99%